Growth and timber quality of Tectona grandis in high input plantations of Costa Rica - Pérez Cordero, L.D.; Kanninen, M. (2003)
Linking forest management to timber industry requirements is fundamental. Connections of silvicultural activities with wood quality are often limited to size-related characteristics, such as minimum DBH. Restrictions set by international markets (e.g. minimum log dimensions, heartwood content and wood defects) limit seriously the marketing options of several forest companies in Costa Rica and many other countries in the area. Therefore, efficient management practices are urgently needed to lead not only to a maximization of per-hectare volume but also to the production of desirable individual-tree dimensions and high quality commercial timber. This paper discusses following topics: aboveground biomass and the applicability on stand density management; wood quality of young and advance aged plantations; effects of stand density on wood quality, results from a thinning trial; effects of stand density on growth and yield, results from a thinning trial; preliminary pruning program, pruning intensity and timing; and total and merchandable volume equations.